Perspectives on gender and work - King, Eden; Roberson, Quinetta M.; Hebl, Michelle R. (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"Few time periods in the past five decades match the intensity of intergroup conflict that people around the world are currently experiencing. Polarized attitudes around various sociopolitical issues, such as gender equality and immigration, have dominated the media and our lives. Furthermore, these powerful social dynamics have also impacted the places where we work and intensified existing strains on workers and workplaces. To address these issues and improve organizational climates, more theories, research and collaborations to understand these phenomena are needed. The volumes in this series will describe and instigate scholarship that advances our understanding of diversity in organizations. In recognition of the centennial anniversary of the ratification of the 19th Amendment to the U.S. Constitution, which granted American women the right to vote, this volume features the personal narratives of recognized scholars in the field who have advanced understanding of gender at work. In this way, we appreciate, and gain perspective on, the rewards and challenges of this essential scholarship and the lives of those who engage in it. The combination of these narratives is an exciting and meaningful exploration of the study of gender at work that authentically captures the experiences of scholars in the field and inventively pushes our understanding of diversity in organizations"-- Provided by publisher.
Keywords: Sex discrimination in employment.; Sex role in the work environment.; Women -- Employment.; Diversity in the workplace.; Business & Economics -- Women in Business.; Office and workplace.; Business and Management.; Gender studies: women and girls.; elektronické knihy; electronic books